The influence of green marketing on the Worten customer - Vinha, Maria Beatriz Faria de Nogueira (2020)
Continued shortage and overuse of natural resources have brought catastrophic environmental consequences that have led to ecosystem degradation, species extinction and, climate change. As a result, environmental concern is continuously increasing, which is highly visible in the new priorities, trends, and habits of the new consumer that has never been so green. Consequently, sustainability is becoming more and more important for organizations that want to address consumer needs by taking their responsibility and minimizing their environmental impact while adding a social contribution. Green marketing (GM) is the tool that allows to promote a social and ecological corporate awareness and gain competitive advantages such as improving corporate environmental performance, image, and reputation. For this, it must be effectively and consistently managed. Nevertheless, although GM is an increasingly common practice within businesses, in general, organizations do not evaluate the impact of the brand's GM on the customer. Thus, this study focuses on understanding the influence of GM on the Worten consumer. A leading electronics consumer company which, although it has a strong and coherent environmental program, lacks knowledge of its effect on its customer. This represents the problem submitted by the green retailer that was researched and answered. The main results achieved led to the conclusion that there is a strong environmental concern reflected in the Worten consumer's predisposition to adopt green behaviors and consumption decisions despite the constraining price barrier. However, the Worten customer is unaware and not engaged in the brand's green efforts mainly due to the company's difficulty in communicating them effectively to its customer. Finally, five improvement proposals in this regard are suggested.